Fan Translating Non-Equivalent Idioms: A Comparative Study of the Strategies Used in the Two Finnish Translations of All The Young Dudes - Syvänperä, Klaara (My University, 2024)
This thesis studies the strategies used by fan translators to translate non-equivalent idioms, using the popular fanfiction work All the Young Dudes by MsKingBean89, and its two Finnish translations by backtoseigfried and h0rnedserpent as the material. The study uses a comparative and quantitative approach to determine which strategies are most common for fan translators. The purpose of the study is to research the idiomatic translation process and to provide further research specifically on non-professional translation processes. The data for this study consists of seven chapters selected from the fanfiction work, 25 idioms found therein and their two Finnish translations. The data was collected by reading these seven chapters and collecting from them all the idioms that have no lexical equivalents in Finnish. After the data collection, the idioms were divided into two groups defined by Chitra Fernando; literal idioms and semi-idioms, and their translations were marked with an adequate translation strategy. These strategies were primarily based on Mona Baker’s translation strategies for idioms, which are used as the theoretical framework in this thesis, and two additional categories were added to facilitate the analysis and to provide an adequate strategy for each translation. The findings section focuses on the most common strategies as well as common patterns in specific translation situations, showing examples from the data. This thesis concluded that paraphrasing the idioms was the most popular strategy used for the translation of non-equivalent idioms by these fan translators. After paraphrasing, the most common was the use of a Finnish idiom which has a different form but a similar idiomatic meaning and the literal translation of every lexical item in the idiom. No significant differences were found between the choices of the translators other than a greater number of translations with a Finnish idiom with a similar idiomatic meaning by backtoseigfried, while h0rnedserpent used a more diverse range of strategies.
Keywords: fan translation, non-equivalence, idioms, translation strategies